The Influence of Entrepreneurial Motivation on Entrepreneurial Interest of UMM Students - Tsabita Khwarazmita (Journal of Career and Entrepreneurship, 2022)
This study seeks to develop research on the concept of motivation and interest in entrepreneurship by students who are expected to become young entrepreneurs to support reducing unemployment and improving the country's economy. This study aims to examine the concept of entrepreneurial motivation on entrepreneurial interest in students at the University of Muhammadiyah Malang. The study population was 500 consisting of all students of the University of Muhammadiyah Malang class 2017. The number of samples used was 63 as respondents using the accidental sampling method for the sampling technique. The data is processed using SmartPLS 3.0. The results of the study indicate that entrepreneurship motivation has an effect on student interest in entrepreneurship at the University of Muhammadiyah Malang. That is, the stronger the entrepreneurial motivation, the stronger the student's entrepreneurial interest.